RADIO PEMERINTAH DAERAH SEBAGAI INSTRUMEN PEMERINTAH DAERAH DALAM PEMENUHAN HAK KONSTITUSIONAL WARGA NEGARA UNTUK MEMPEROLEH INFORMASI - Asri Lasatu (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
Information is a basic human need in the development of personality and social environment and part of national security. Information has been declared human rights by the United Nations Assembly, and is a constitutional right of every Indonesian citizen. Therefore, the state is obliged to guarantee every citizen to obtain good information. To provide information to the public, Local Government Radio is an effective and efficient instrument because its frequency reaches to remote areas. In this connection, a study of the existence of Local Government Radio as an instrument of the regional government was carried out in fulfilling the constitutional rights of citizens to obtain information. The results of the study concluded that the Regional Government Radio can realize the constitutional rights of citizens to obtain information as long as its implementation is based on the principle of independent, neutral and non-commercial, and oriented to public services to obtain information. Keyword: Local Government Radio, Information, Constitutional Rights.